2016
DOI: 10.26719/2016.22.10.756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal variation of human intestinal parasites in patients attending hospital with abdominal symptoms in northern Jordan

Abstract: This study was carried out to determine the prevalence of intestinal parasites and their seasonal variation in northern Jordan. A total of 21 906 stool samples were collected over a period of 4 years (2009)(2010)(2011)(2012)(2013) from 5 government hospitals in 3 cities. Samples were processed and examined microscopically and by concentration methods. Parasitic infection was found in 9611 samples (44%). Giardia lamblia was the most prevalent parasite (41%) followed by Entamoeba histolytica (31%) and Ent. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
9
17
0
Order By: Relevance
“…This study showed that the chances of males contracting infections are 1.8 times higher compared to females but marginally insignificant (P=0.07, CI: 0.82-3.95). This agrees with some of the studies cited just above [20,30,35]. This study indicated that age had no effect on infections caused by parasites of the species G. lamblia, E. nana and E. coli but those of G. lamblia were affected by hosts' gender as also reported elsewhere [30,42].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study showed that the chances of males contracting infections are 1.8 times higher compared to females but marginally insignificant (P=0.07, CI: 0.82-3.95). This agrees with some of the studies cited just above [20,30,35]. This study indicated that age had no effect on infections caused by parasites of the species G. lamblia, E. nana and E. coli but those of G. lamblia were affected by hosts' gender as also reported elsewhere [30,42].…”
Section: Discussionsupporting
confidence: 93%
“…In the West Bank, the incidence rate of parasitic infections in the same year was 69 per 100,000 with an actual total of 1,881 infections [13]. with an approximate incidence rate of 148 per 100,000 caused by seven parasitic species and like our study showed the species G. lamblia to be the most prevalent parasite with rare (<1%) infections caused by the species H. nana and Chilomastix mesnili [35]. Multiple intestinal parasitic infections increase the burden of disease and were recorded at a rate of 46% in Palestine of the 1940s.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…children are only recruited within one month). Many previously conducted studies have witnessed that the prevalence of several STHs in the human population is subjected to inter-seasonal variability [41,42].…”
Section: Limitation Of the Studymentioning
confidence: 99%
“…Due to the cross-sectional nature of the study we could not be able to capture the seasonal variations in the prevalence of intestinal parasitosis. Previous studies have witnessed that prevalence of many intestinal parasites in human population is subjected to inter-seasonal fluctuation [33,34]. Further, as the study was limited to pregnant women attending ANC, the findings may not be directly extrapolated to pregnant women devoid of prenatal care.…”
Section: Discussionmentioning
confidence: 98%